2017
DOI: 10.3847/1538-4357/aa8867
|View full text |Cite
|
Sign up to set email alerts
|

No Neon, but Jets in the Remarkable Recurrent Nova M31N 2008-12a?—Hubble Space Telescope Spectroscopy of the 2015 Eruption

Abstract: The 2008 discovery of an eruption of M31N 2008-12a began a journey on which the true nature of this remarkable recurrent nova continues to be revealed. M31N 2008-12a contains a white dwarf (WD) close to the Chandrasekhar limit, accreting at a high rate from its companion, and undergoes thermonuclear eruptions that are observed yearly and may even be twice as frequent. In this paper, we report on Hubble Space Telescope Space Telescope Imaging Spectrograph ultraviolet spectroscopy taken within days of the predic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 63 publications
1
19
0
Order By: Relevance
“…The FUV spectrum, taken 3.32 days post-eruption was much more fruitful. Darnley et al (2017b) reported that the FUV spectrum was broadly consistent with that expected from a CO WD (see, e.g., Shore, 2012) and importantly there was no evidence for any neon in the ejecta at that time. The FUV lines also exhibited very high velocities and the resonance lines remained optically thick (and saturated in some cases), the profile of the N v line (the highest ionisation energy line observed) was shown to be consistent with optically thick outflows or jets.…”
Section: 2014 and 2015 And A Six Month Recurrence?mentioning
confidence: 62%
See 1 more Smart Citation
“…The FUV spectrum, taken 3.32 days post-eruption was much more fruitful. Darnley et al (2017b) reported that the FUV spectrum was broadly consistent with that expected from a CO WD (see, e.g., Shore, 2012) and importantly there was no evidence for any neon in the ejecta at that time. The FUV lines also exhibited very high velocities and the resonance lines remained optically thick (and saturated in some cases), the profile of the N v line (the highest ionisation energy line observed) was shown to be consistent with optically thick outflows or jets.…”
Section: 2014 and 2015 And A Six Month Recurrence?mentioning
confidence: 62%
“…Evidence for interacting ejecta from successive RN eruptions has been presented for T Pyxidis (Shara et al, 1997;Toraskar et al, 2013). As a proof of concept, Darnley et al (2019b) presented a hydrodynamical simulation (based on the Morpheus code; 21 Who identifies a "Miss (Vera Marie) Gushee" as the photographer. Vaytet et al, 2007) of 100,000 annual eruptions of 12a.…”
Section: The Super-remnantmentioning
confidence: 99%
“…This is the best candidate for a type Ia supernova explosion, because the deduced mass of the white dwarf is extremely close to the Chandrasekhar limit (Kato et al 2014;Hachisu et al 2016), but its chemical composition should be CO and not ONe. From the observational point of view, HST observations of the 2015 eruption of M31N 2008-12a yielded non detection of Neon, which may be indicative of a CO white dwarf (Darnley et al 2017a). Theoretically, the white dwarf of M31N 2008-12a could reach near-Chandrasekhar-mass through successive eruptions with an initial CO core (Hillman et al 2016).…”
Section: Classical Novaementioning
confidence: 99%
“…The arcs in the Z Cam system differ from the blobs in the SMSSJ1305-2931 system in that their spectra show definite emission lines of Hα and [Nii] and [Oii] (Shara et al 2007). Yet it is conceivable that a classical nova (or a recurrent nova -see Darnley et al (2017)) eruption also occurred in the SMSSJ1305-2931 system in the past, and that the blobs are the last remaining features from that eruption. Mason et al (2018) point out in their detailed study of four novae that the ejecta properties are in all cases consistent with "clumpy gas expelled during a single, brief ejection episode and in ballistic expansion" confined within a bi-conical geometry (Mason et al 2018).…”
Section: Are the Blobs Outflow Relics?mentioning
confidence: 99%
“…In that context it is also worth noting that at least some novae have been shown to have complex post-eruption structures, including multiple components, collimated outflows and high-velocity features (e.g. Darnley et al 2017;Woudt et al 2009). Further, Mróz et al (2016) have shown that after a nova eruption, the white dwarf has a higher accretion rate than before the nova outburst, for a period of order hundreds of years.…”
Section: Are the Blobs Outflow Relics?mentioning
confidence: 99%